Rebel fire - Lane, Andy (Sherlock Holmes. The legend begins, 2012)
In 1868, teenaged Sherlock Holmes discovers that his American tutor is hunting a notorious killer who was supposedly killed by the United States government, but who is apparently alive and well in Surrey, England.